2021
DOI: 10.21203/rs.3.rs-1118972/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Determining Customer Satisfaction with Counter Services of Local Government Offices: On-Site Survey Examining Service Quality at Higashihiroshima City Hall, Japan

Abstract: This study empirically investigated the major factors determining customer satisfaction with counter services in local government offices in Japan, comparing them with the results of similar surveys conducted by the author in 2020. This study considers visitors’ direct experience of counter services through an on-site survey conducted at a municipal government building, referring to (1) customer satisfaction research in various countries, especially the expectancy disconfirmation model; (2) the SERVQUAL model;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…The regression coefficients for each variable indicated that service delivery quality (category C) was the most important variable. This result was consistent with Moteki's (2021a;2021b) results in Japan, which revealed that service delivery was more important than administrative services. In contrast, the results of the 2020 survey at the Kurose branch office of the Higashihiroshima city government showed that the human factor was the most influential.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The regression coefficients for each variable indicated that service delivery quality (category C) was the most important variable. This result was consistent with Moteki's (2021a;2021b) results in Japan, which revealed that service delivery was more important than administrative services. In contrast, the results of the 2020 survey at the Kurose branch office of the Higashihiroshima city government showed that the human factor was the most influential.…”
Section: Discussionsupporting
confidence: 91%
“…The results of this survey of Tokyo Metropolitan Area ward office users were consistent with the author's surveys conducted at Osaka City Ward Office (Moteki, 2021a) and Higashihiroshima City Hall (Moteki, 2021b). This study conducted an online survey targeting female users of the ward offices.…”
Section: Discussionsupporting
confidence: 80%
“…In this study, we plan to conduct an on-site survey by modifying Moteki's three-section question scale of the on-site survey [17], and Moteki's online survey [18], both of which are surveys of governmental institutions; we shall also use our own three-section question framework of facilities and equipment, staff response, and exhibition content. The self-administered questionnaire survey at the Higashihiroshima City Museum of Art in Summer 2022 will target visitors after they have viewed the special collection.…”
Section: Methodsmentioning
confidence: 99%
“…The public service organizations should introduce appropriate and realistic accountability measures; and work together in preparation of their rules, regulations, and procedure consistently so that they would have better integration, which enable them to provide good service delivery to their customers. Moteki, Yasutoshi. (2021) investigated the major factors determining customer satisfaction with counter services in local government offices in Japan, comparing them with the results of similar surveys conducted by the author in 2020.…”
Section: Review Of Previous Literaturementioning
confidence: 99%